Participant Retention in a Randomized Clinical Trial in an Outbreak Setting: Lessons From the Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE). (18th May 2018) - Carter, Rosalind J; Senesi, Reynold G B; Dawson, Peter; Gassama, Ibrahim; Kargbo, S A S; Petrie, Carey R; Rogers, Mohamed Hashim; Samai, Mohamed; Luman, Elizabeth T
Abstract: The Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE), a phase 2/3 trial of an investigational Ebola vaccine, was implemented in April 2015 in Sierra Leone. Healthcare and Ebola frontline workers were randomized to immediate (within 7 days) or deferred (18–24 weeks) vaccination and observed from enrollment to 6 months postvaccination for safety and Ebola virus disease. There were concerns that high retention and compliance would be difficult to achieve, particularly for the deferred group. Trial staff conducted monthly calls to participants and home visits if needed. Retention was defined as completion of the final assessment at 6 months postenrollment and postvaccination. Full compliance was defined as completion of all monthly assessments before and 6 months after vaccination and vaccination per protocol. Logistic regression was used to identify demographic characteristics associated with these outcomes. Of 8626 participants enrolled, 7979 (92.5%) were retained postenrollment (95.2% in immediate vaccination arm, 89.8% in deferred arm). Overall, 68.8% were fully compliant postenrollment (73.4% in immediate arm, 64.2% in deferred arm). Among 7979 vaccinated participants, 95.9% were retained 6 months postvaccination, with no significant difference between study arms. Frontline workers and younger participants were least likely to be retained and had a lower likelihood of full compliance. High retention of participants in a vaccine clinical trial in a low-resource setting, even among those assigned to deferred vaccination, was achievable. Younger participants and frontline workers may require additional follow-up strategies and resources. Clinical Trials Registration: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].